Peanut avoidance and peanut allergy diagnosis in siblings of peanut allergic children. Issue 1 (January 2015) - Lavine, E.; Clarke, A.; Joseph, L.; Shand, G.; Alizadehfar, R.; Asai, Y.; Chan, E. S.; Harada, L.; Allen, M.; Ben‐Shoshan, M.
Summary Background Studies suggest that siblings of children with peanut allergy (PNA) have a higher prevalence of PNA than the general population. Objectives The Canadian Peanut Allergy Registry was used to assess the percentage of siblings of registered index PNA children who were 1) never exposed to peanut or 2) reportedly diagnosed with PNA by a physician without either a history of allergic reaction or a confirmatory testing. Sociodemographic and clinical factors that may be associated with either outcome were evaluated. Methods Parents completed a questionnaire on siblings' sociodemographic characteristics, exposure and reaction to peanut, confirmatory tests performed and whether PNA had been diagnosed. Results Of 932 Registry families, 748 families responded, representing 922 siblings. 13.6% of siblings had never been exposed to peanut, 70.4% (n = 88) of which were born after the index child. Almost 9% of siblings (80) were reported as PNA, but almost half of this group had no history of an allergic reaction to peanut, including five children who also had no testing to confirm PNA. Of these 5, 4 were born after PNA diagnosis in the index child. In a multivariate regression analysis for siblings at least 3 years old, those born after PNA diagnosis in the index child were more likely to have never been exposed to peanut. In a univariate analysis, siblings born after the diagnosis of PNA in the index child were more likely to be diagnosed with PNA without supportive history or confirmatory testing. Conclusions and Clinical Relevance These data estimate that more than 10% of siblings of PNA patients will avoid peanut and that siblings born after the diagnosis of PNA in an index child are more likely to have never been exposed. Educational programs and guidelines that caution against unnecessary avoidance are required.